2014
DOI: 10.5665/sleep.3306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Sleep Fragmentation on Wake-Active Neurons and the Hypercapnic Arousal Response

Abstract: Four weeks of sleep fragmentation (SF4wk) impairs arousal responses to hypercapnia, reduces wake neuron projections and locus coeruleus neuronal excitability, supporting the concepts that some effects of sleep fragmentation may contribute to impaired arousal responses in sleep apnea, which may not reverse immediately with therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 69 publications
4
60
1
1
Order By: Relevance
“…In OSAS patients, the consequence of SF or chronic blood gas disturbance may underlie the lack of response to continuous theta burst stimulation, suggesting impaired long-term depression-like neuroplasticity in these subjects [26]. Moreover, the effects of chronic SF have been also tested in adult male mice undergoing orbital platform SF [27]. The authors found that four weeks of SF impairs arousal responses to hypercapnia and reduces wake neuron projections and locus coeruleus neuronal excitability, supporting the concept that some effects of SF may contribute to impaired arousal responses in sleep apnea.…”
Section: Discussionmentioning
confidence: 98%
“…In OSAS patients, the consequence of SF or chronic blood gas disturbance may underlie the lack of response to continuous theta burst stimulation, suggesting impaired long-term depression-like neuroplasticity in these subjects [26]. Moreover, the effects of chronic SF have been also tested in adult male mice undergoing orbital platform SF [27]. The authors found that four weeks of SF impairs arousal responses to hypercapnia and reduces wake neuron projections and locus coeruleus neuronal excitability, supporting the concept that some effects of SF may contribute to impaired arousal responses in sleep apnea.…”
Section: Discussionmentioning
confidence: 98%
“…OSA-related sleep fragmentation also has detrimental effects on the brain. It has been implicated in decreased neuronal excitability in regions including the locus coeruleus [23]. Additionally, sleep fragmentation due to OSA could impair homeostatic effects of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Although more frequent arousals are associated with risk of hypertension and can adversely affect the cardiovascular system, 33 34 arousals may also serve as a protective mechanism to terminate apnoeic episodes. 35 In fact, a low arousal index has been linked to increased risk for brainstem white matter disease and incident stroke. 8 36 Thus, two distinct pathophysiological scenarios are plausible-that is, while frequent arousals may indicate excessive sympathetic activation, low arousal responses may reflect abnormalities in autonomic control, respiratory reflexes, or result from chronic sleep fragmentation.…”
Section: Arousal Index and Afmentioning
confidence: 99%